Simulation and experimental verification of new universal power amplifiers. (2nd February 2010) - Dalapati, Suvarun; Chakraborty, Chandan
A new class of DC/DC and DC/AC power amplifier is the subject of this paper. The proposed power converters work on the basis of charging a capacitor in a controlled manner to synthesise any waveform at the output from the regulated/unregulated DC voltage at the input. This paper first reports the principle of operation of such waveform synthesiser and then proceeds to detail the performance of typical DC/DC and DC/AC power conversion at regulated voltages. PSPICE based simulations are reported to explore the idea and experimental results from laboratory-prototype are also added to confirm the usefulness of the proposed concept.